Close Up at a Distance: Mapping, Technology, and Politics - Kurgan (MIT Press, 2013)
Monograph
fulltext
Keywords: Aerospace; Communication, Networking and Broadcast Technologies; Computing and Processing; Signal Processing and Analysis; Transportation